Dispersion of hydroxyapatite nanoparticles in natural rubber latex and poly lactic acid based matrices - Cesar, Mariana Biondi [UNESP]; Poli, Hamish; Piazza, Rodolfo Debone [UNESP]; Marques, Rodrigo Fernando Costa [UNESP]; Herculano, Rondinelli Donizetti [UNESP]; Grøndahl, Lisbeth (Wiley, 2022)
Hydroxyapatite (HAp)-polymer composite materials are of interest for materials that interface with or substitute bone tissue. HAp nanoparticles (length 290 nm, width 56 nm) synthesized by a wet chemical method were incorporated (5 wt%) into natural rubber latex (NRL), poly lactic acid (PLA) and NRL/PLA (75/25) solvent cast films using three different methods: dry nanoparticles; a dispersion prepared from dry nanoparticles; a dispersion prepared through solvent exchange. Common to all composite materials were an improvement in the contact angle by 10%–13% and a reduction in the elongation at break from 430% to 330%–370%. Furthermore, the method of HAp incorporation influenced the properties of the material with the use of dioxane suspension improving the homogeneity of the films as evidenced from visual appearance and SEM. This led to slower water uptake and higher thermal stability with a shift in the PLA melting peak from 296°C to 334°C when compared to pure polymer and composites with poorly dispersed particle.